The best teacher in you how to accelerate learning and change lives - Quinn, Robert E.; Heynoski, Katherine; Thomas, Mike; Spreitzer, Gretchen (San Francisco Berrett-Koehler Publishers, 2014)
"What turns ordinary teachers into highly effective teachers? How are great teachers able to ignite the love of learning among their students, accelerate that learning, and change students' lives? What does teaching look like at its very best? This book provides the best researched and most revealing answers to these questions"--Provided by publisher.
Keywords: Effective teaching; Reflective teaching; Motivation in education